A survey on knowledge, initiation and usage of electronic cigarette among students in a private university, Kajang - Lee, Zhi Han (2020)
Electronic cigarette, a relatively new device that produce vaporised nicotine has sparked throughout the world. The sudden increase in popularity and use of e-cigarette has become the most concerning aspects particularly among young adults, despite the safety and usefulness of e-cigarette are still remain unknown. The present study aim to determine knowledge, reasons for initiation, usage on e-cigarettes and the associations between the selected variables with e-smoking status among university students between the age of 18-24 years. This survey was conducted among the convenience sample of a private university, Kajang, Malaysia during the end of February to March 2020. In total of 312 participants were recruited using adapted and validated questionnaire. Data entry were done by Statistical Package for Social Sciences (SPSS) 23 and analysed using descriptive and inferential statistic. Data revealed, 169 (57.5%), of participants had used e-cigarette and, 149 (50.7%), had good knowledge on e-cigarettes. Further findings showed the main reasons for initiations of e-cigarette were due to e-cigarettes are accessible, more acceptable to non-tobacco smokers, affordable and effective in quitting smoking. Chi square analysis reveals that there was an association between socio-demographic variables (faculty and cigarette smoking status) with esmoking status, [χ2 (8, n=294) = 40.615, p < 0.001] and [χ2 (4, n=294) = 148.045, p < 0.001] respectively. As for association between usage of e-cigarettes (ever usage, peer influence, frequency of using e-cigarettes) with e-smoking status it was similarly significant, [χ2 (4, n=294) = 249.000, p < 0.001], [χ2 (1, n=169) = 8.101, p = 0.004], [χ2 (1, n=169) = 175.085, p < 0.001] and [χ2 (1, n=169) = 33.409 p < 0.001]. However, for the association between knowledge with esmoking status results was not significant. E-cigarette use is prevalent among university students and it poses a significant health harm to the users. In view of the outbreak of vaping related lung injuries and potential nicotine addiction present study has highlighted the necessity for more useful research to prove the safety and effectiveness on e-cigarettes. Ongoing monitoring on the knowledge, latest usage trends and the reason for using are needed urgently.